Alternative Strategy Based on Scanning Probe Lithography for Patterning Complex Metallic Nanostrutures on Rigid or Flexible Substrates. Issue 11 (25th July 2018) - Edely, Mathieu; Delorme, Nicolas; Siniscalco, David; Bardeau, Jean‐François
Abstract: An efficient methodology based on scanning probe lithography technique to design complex metallic nanostructures on rigid or flexible substrates is reported. This maskless method is based on an atomic force microscopy nanoindentation technique for engraving predetermined patterns on a polymer film and creating inverted patterns on the metal surface. The present work then demonstrates that this methodology opens up new possibilities of applications for which an individual control of the height, shape, and periodicity of each printed nano(micro)structure is necessary. The possibilities of the presented method are defined in terms of resolution, height, and shape of the metallic nanostructures and speed of writing. The ability to reproduce 3D arrangement of gold nanostructures allows to create nanostructured substrates for surface‐enhanced Raman scattering (SERS) applications. The potential of the substrate for biosensing and the effect in particular of the periodicity of the nanostructures are explored by the SERS measurement after immersion of the substrate in a solution of 10 −6 m thiophenol. Abstract : An alternative strategy for patterning complex metallic nanostructures on rigid or flexible substrates is presented. The method opens up new possibilities of applications for which an individual control of the height, shape, and periodicity of each printed nano(micro)structure is necessary. The ability to reproduce 3D arrangement of gold nanostructures allows to create efficient nanostructured substrates for SERS applications.